A novel nonsense and inactivating variant of ST3GAL3 in two infant siblings suffering severe epilepsy and expressing circulating CA19.9. (4th October 2019) - Indellicato, Rossella; Domenighini, Ruben; Malagolini, Nadia; Cereda, Anna; Mamoli, Daniela; Pezzani, Lidia; Iascone, Maria; dall'Olio, Fabio; Trinchera, Marco
Abstract: Three missense variants of ST3GAL3 are known to be responsible for a congenital disorder of glycosylation determining a neurodevelopmental disorder (intellectual disability/epileptic encephalopathy). Here we report a novel nonsense variant, p.Y220 *, in two dichorionic infant twins presenting a picture of epileptic encephalopathy with impaired neuromotor development. Upon expression in HEK-293T cells, the variant appears totally devoid of enzymatic activity in vitro, apparently accumulated with respect to the wild-type or the missense variants, as detected by western blot, and in large part properly localized in the Golgi apparatus, as assessed by confocal microscopy. Both patients were found to efficiently express the CA19.9 antigen in the serum despite the total loss of ST3GAL3 activity, which thus appears replaceable from other ST3GALs in the synthesis of the sialyl-Lewis a epitope. Kinetic studies of ST3GAL3 revealed a strong preference for lactotetraosylceramide as acceptor and gangliotetraosylceramide was also efficiently utilized in vitro. Moreover, the p.A13D missense variant, the one maintaining residual sialyltransferase activity, was found to have much lower affinity for all suitable substrates than the wild-type enzyme with an overall catalytic efficiency almost negligible. Altogether the present data suggest that the apparent redundancy of ST3GALs deduced from knock-out mouse models only partially exists in humans. In fact, our patients lacking ST3GAL3 activity synthesize the CA19.9 epitope sialyl-Lewis a, but not all glycans necessary for fine brain functions, where the role of minor gangliosides deserves further attention.